Sanctions Against Working Groups for the Selection of Goods/Services Providers in Cases of Tender Collusion (Study: Comparison between Indonesia and Malaysia) - Bukit, Liametami Benedicta; Sugiyono, Heru (Universitas Muhammadiyah Sidoarjo, 2025)
The general background of this study is the persistent dominance of tender collusion in Indonesia’s procurement sector, which undermines fair competition and public welfare. The specific background focuses on KPPU Decision No. 15/KPPU-L/2023, where the Working Group (POKJA) was proven negligent but exempted from sanctions due to its unclear legal status under Law No. 5/1999. The knowledge gap lies in the absence of explicit regulatory authority to sanction POKJA, creating ambiguity in defining “other parties” within tender collusion provisions. The aim of this research is to compare Indonesia’s regulatory framework with Malaysia’s system, which empowers MYCC to impose administrative sanctions directly on public officials involved in bid rigging. The results show that Malaysia’s Competition Act 2010 provides broader investigative and enforcement powers, enabling more effective deterrence, while Indonesia relies on fragmented administrative mechanisms that weaken accountability. The novelty of this study is its comparative legal analysis demonstrating how dual-authority competition bodies enhance integrity in public procurement. The implications highlight the urgency to revise Law No. 5/1999, clarify POKJA’s legal standing, and establish expert data-analysis bodies to strengthen preventive measures against future tender collusion. Highlights: Indonesia’s weak sanctioning framework leaves POKJA’s accountability unclear in tender collusion cases. Malaysia’s MYCC demonstrates stronger enforcement through integrated administrative and public powers. Reform of Law No. 5/1999 is essential to strengthen oversight and prevent future bid-rigging practices. Keywords: Tender Collusion, POKJA, Competition Law, MYCC , Procurement Governance